Association of CYP3A polymorphisms with the pharmacokinetics of cyclosporine A in early post-renal transplant recipients in China - Meng, Xiang-guang (Nature Publishing Group, 2012)
AIM: To evaluate retrospectively the association of cytochrome P450 3A (CYP3A) and ATP-binding cassette sub-family B member 1 (ABCB1) gene polymorphisms with the pharmacokinetics of cyclosporine A (CsA) in Chinese renal transplant patients. METHODS: One hundred and twenty-six renal transplant patients were recruited. Blood samples were collected, and corresponding clinical indices were recorded on the seventh day after the procedure. The patients were genotyped for CYP3A4*1G, CYP3A5*3C, ABCB1 1236 C>T, ABCB1 2677 G>T/A, and ABCB1 3435 C>T polymorphisms. Whole blood trough concentrations of CsA at time zero (C(0)) were measured before the drug administration. A multiple regression model was developed to analyze the effects of genetic factors on the CsA dose-adjusted C(0) (C(0)/dose) based on several clinical indices. RESULTS: The CYP3A5*3C polymorphism influenced the C(0) and C(0)/dose of CsA, which were significantly higher in patients with the GG genotype than in patients with the AA or GA genotypes. No significant differences were detected for other SNPs (CYP3A4*1G, ABCB1 1236 C>T, ABCB1 2677 G>T/A, and ABCB1 3435 C>T). In a univariate analysis using Pearson's correlation test, age, hemoglobin, blood urea nitrogen and blood creatinine levels were significantly correlated with the log-transformed CsA C(0)/dose. In the multiple regression model, CYP3A5*3C, age, hemoglobin and blood creatinine level were associated with the log-transformed CsA C(0)/dose. CONCLUSION: CYP3A5*3C correlates with the C(0)/dose of CsA on the seventh day after renal transplantation. The allele is a putative indicator for the optimal CsA dosage in the early phase of renal transplantation in the Chinese population.